Cytokine levels in human synovial fluid during the different stages of acute gout: role of transforming growth factor β1 in the resolution phase. Issue 4 (30th January 2012) - Scanu, Anna; Oliviero, Francesca; Ramonda, Roberta; Frallonardo, Paola; Dayer, Jean-Michel; Punzi, Leonardo
Abstract : Objectives: To determine the most relevant parameters in synovial fluid (SF) during the various stages of acute gout. Methods: SFs from 38 gouty patients were analysed for white blood cell (WBC) count, percentage of polymorphonuclear cells (PMNs) and levels of interleukin 1β (IL-1β), IL-6, IL-8, tumour necrosis factorα (TNFα) and transforming growth factor β1 (TGFβ1). Patients were divided into three groups according to the length of time since onset of the attack: phase I (0–48 h), phase II (days 3–4) and phase III (days 5–7). Results: Levels of WBCs were similar in SFs from phases I and II, while phase III showed the lowest WBC count. Percentages of PMNs were raised in all SFs. None of the cytokines analysed differed between phases I and II except for TGFβ1, which was higher in phase II. IL-1β, IL-6 and TNFα were higher in group 1 than in group 3. Levels of all the cytokines assessed, with the exception of TGFβ1, were significantly lower in phase III than in phase II IL-1β, p<0.05; IL-6, p<0.01; IL-8, p<0.001; TNFα, p<0.05).TGFβ1 levels were highest in SFs from phase III. Conclusion: Cytokine levels in SFs may change depending on the different stages of acute gout, highlighting the role of TGFβ1 in the resolution of gout.